Deteksi Kategori Sampah Menggunakan Metode You Only Look Once - Ja'far, Ja'far; Udjulawa, Daniel (Algoritme Jurnal Mahasiswa Teknik Informatika, 2025)
Waste is the residue generated from human daily activities or natural processes that is no longer needed. According to data from the Ministry of Environment and Forestry, waste generation in Indonesia reaches 36 million tons per year, with unmanaged waste totaling 13 million tons annually. Inadequate waste management can lead to various issues. One significant source of unmanaged waste is found in schools, attributed to lack of awareness and low concern, resulting in student’s laziness in disposing of waste properly. This project aims to develop a system that assists students in identifying specific waste categories and incorporates a royalty points system to boost student motivation. The method employed is You Only Look Once Version 5 with the Darknet architecture, utilizing an 80% training, 10% validation, and 10% testing dataset split. The results of testing this method at the development stage showed a recall value of 92.4%, precision of 88.4%, and mAP of 96.4%. Meanwhile, at the implementation stage on smartphones, the recall value reached 89.9% with a precision of 94.2%, and an average detection speed of around 1.68 seconds.